A novel mobile web application for an integrated medical and emergency model - Hameed, Shihab A.; Chek Noh, Noor Hafiza; Salim, NurHuda; M. Sharifudeen, Shahina Shabnam (2010)
The current situation of medical, healthcare and emergency related system in Malaysia shows that it is mostly separated and not fully computerized. The fully computerizing and combining of medical healthcare and emergency systems will lead to produce a Novel Integrated Medical and Emergency system. This integrated system is being divided into three main parts which is the web based medical and emergency system, intelligent agent, and mobility. The system contains a database that will communicate and cooperated with intelligent agent and mobility. The main drawbacks for the current medical, healthcare, and emergency systems in Malaysia include: Difficulty in searching and reviewing up to date records for patient, doctor, hospital, drug, etc since many of such records are still kept in filing cabinet.